1999
DOI: 10.1023/a:1020607501910
|View full text |Cite
|
Sign up to set email alerts
|

The Intermolecular Disulfide Bridge of Human Glial Cell Line-Derived Neurotrophic Factor: Its Selective Reduction and Biological Activity of the Modified Protein

Abstract: Recombinant human glial cell line-derived neurotrophic factor has been implicated to have therapeutic potential in the treatment of neurodegenerative diseases. The mature protein is a single polypeptide of 134 amino acid residues and functions as a disulfide-linked dimer. Reduction of the protein with dithiothreitol at pH 7.0 and in the absence of denaturant showed that the single intermolecular cystine bridge was reduced preferentially. Direct alkylation of the generated free sulfhydryl group using iodoacetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Sedimentation velocity and equilibrium data clearly demonstrated that C101A GDNF forms a stable non-covalent dimer in solution with a dissociation constant below 1 nM. This is consistent with the observed biological activity of the mutant, which is indistinguishable from the wild-type protein and is also consistent with the activity of GDNF following reduction of the intermolecular disulfide (Hui et al, 1999). These results suggest that the dimerization is a prerequisite for receptor dimerization.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Sedimentation velocity and equilibrium data clearly demonstrated that C101A GDNF forms a stable non-covalent dimer in solution with a dissociation constant below 1 nM. This is consistent with the observed biological activity of the mutant, which is indistinguishable from the wild-type protein and is also consistent with the activity of GDNF following reduction of the intermolecular disulfide (Hui et al, 1999). These results suggest that the dimerization is a prerequisite for receptor dimerization.…”
Section: Discussionsupporting
confidence: 81%
“…The disulfide structure of GDNF was recently determined (Hui et al, 1996), showing that GDNF contains the seven conserved cysteine residues that form the intramolecular disulfide knot characteristic of the TGF-β superfamily, although it shares very little sequence homology with TGF-β2 (Lin et al, 1993). In addition, Cys101 of GDNF was shown to be involved in the intermolecular disulfide bond (Hui et al, 1996(Hui et al, , 1999. The three-dimensional structure of GDNF, determined by X-ray crystallography (Eigenbrot and Gerger, 1997), revealed that the dimeric contact in GDNF is significantly different from that found in TGF-β.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation